The Effect of Communication, Culture and Organizational Commitment on the Performance of Employees in the Ngawi Regency Transportation Service - Heni Setiyoningsih; Mutmainah Mutmainah; Ahadiati Rohmatiah (Jurnal Manajemen dan Profesional, 2026)
This study was conducted to determine the influence of communication, organizational culture, and organizational commitment on the performance of employees at the Ngawi Regency Transportation Agency. To determine the results of the study, a quantitative research type was used by distributing questionnaires. The employee population at this agency was 126 people. The sampling technique in this study used saturated samples. So all populations were used as research samples. To find out the answer to the research objectives, a multiple linear regression analysis technique was used with the help of the SPSS application. The results of the study indicate that communication partially influences employee performance. Meanwhile, organizational culture and organizational commitment do not affect employee performance. Simultaneously, the results of the study indicate that there is an influence between communication, organizational culture, and organizational commitment on employee performance.